Fraudulent act: essence and legal regulation - Hofeld, H. S. (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The article examines current issues of science and practice regarding the definition of the essence, signs and legal regulation of a fraudulent transaction as one of the types of contracts in civil law. The importance of the category of “deeds” for civil law is emphasized. Modern scientific positions on understanding the essence of the “fraudulent act” categories are defined and analyzed. The author’s vision of the understanding of the above-mentioned category is proposed, under which, in a general sense, a transaction is defined where the debtor (as one of the parties) performs dishonest actions in order to avoid fulfilling his or her obligation to the creditor. The necessity of forming a unified approach to defining the essence of the category of fraudulent transaction is emphasized. The principles of civil legislation, which are violated as a result of the conclusion of a fraudulent transaction, and the court practice on this issue are defined. The essence of the violation of the principle of good faith when concluding a fraudulent transaction is clarified. The need to make appropriate changes to the current civil legislation of Ukraine in order to standardize judicial practice and eliminate existing legislative gaps is emphasized. The judicial practice is analyzed and a review of court decisions regarding the fraudulent transaction and its essential conditions is carried out. It has been established that private law instruments should not be used by participants in civil transactions to avoid paying a debt (money, damages, damage) or to execute a court decision on debt collection (money, damages, damage) that has entered into force. The article notes that a fraudulent contract can be both paid and unpaid. A paid fraudulent contract has its own specifics and features that distinguish it from another fraudulent contract (for example, a free one). The right to evil is singled out as a sign of a committed fraudulent act. Further prospective directions of scientific research on certain issues of fraudulent transactions have been established.